Intestinal Dysbiosis in, and Enteral Bacterial Therapies for, Systemic Autoimmune Diseases - Marietta, Eric; Mangalam, Ashutosh K.; Taneja, Veena; Murray, Joseph A. (Frontiers in Immunology, 2020)
Recent studies have shown that a number of common autoimmune diseases have perturbations of their intestinal microbiome (dysbiosis). These include: Celiac Disease (CeD), Multiple Sclerosis (MS), Rheumatoid Arthritis (RA), Sjogren’s Syndrome (SS), and Type 1 diabetes (T1D). All of these have intestinal microbiomes that are different from healthy controls. There have been numerous studies using animal models of single probiotics (monoclonal) or mixtures of probiotics (polyclonal) and even complete microbiota transfer (fecal microbial transfer-FMT) to inhibit or delay the onset of autoimmune diseases such as the aforementioned common ones. However, fewer clinical trials have utilized monoclonal therapies or FMT than polyclonal therapies for treating autoimmune diseases, even though bacterial mono-therapies and FMT do inhibit the development and/or delay the onset of disease in rodent models of those autoimmune diseases. In this review then, we review the previously completed and currently ongoing clinical trials that are testing bacterial therapies (FMT, monoclonal, and polyclonal) to treat common autoimmune dseases and discuss the successes in using bacterial monotherapies to treat rodent models of these common autoimmune diseases.